Impact of Underpricing Determinants on Market Return of S&P BSE SME IPO in India - Anbukarasi, M.; Kanmani, M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Primary capital market i.e. Initial Public Offering (IPO) market forms a significant part of it. India, an emerging market, has seen tremendous growth in the BSE SME IPO market over the past few years. In light of this, the Underpricing of BSE SME IPOs is being examined. This study aims to investigate and Analyze the determinants of Underpricing of BSE SME IPOs in the India. This study examines the cause-and-effect relationship and Impact of Raw Return and Market Adjusted Excess Return between Issue Price, Issue Size, Lot Size , Market Return and Volatility of BSE SME IPOs of Underpricing in India. There is a significant relationship between Raw Return and Market Adjusted Excess Return between lot size, volatility, market return, issue size, issue price of S&P BSE SME IPO.The null hypothesis is rejected at 5% level of significant for the Specific variables among Raw Return and Market Adjusted Excess Return in the Study Period.While investing in an S&P BSE SME IPO the investor should be careful and they may choose long-term investment because there is a low risk and they can earn a return at longtime.The Present Study Provides a detailed analysis of S&P BSE SME IPO in India and Underpricing of Raw Return and Market Adjusted Excess Return relationship and impact for 10 years January 2013 to December 2022 by taking a yearly observation. At the same time,they have a Strong Relationship between the issue-specific and market-specific variables like volatility and market return and integrated with each other